MSC-Derived Small Extracellular Vesicles Attenuate Autoimmune Dacryoadenitis by Promoting M2 Macrophage Polarization and Inducing Tregs via miR-100-5p - Li, Na; Gao, Zhiqi; Zhao, Lu; Du, Bei; Ma, Binyun; Nian, Hong; Wei, Ruihua (Frontiers in Immunology, 2022)
Background Mesenchymal stem cell-derived small extracellular vesicles (MSC-sEVs) have been increasingly proved as promising immunomodulators against some autoimmune disorders. However, the possible effect and the underlying mechanism of MSC-sEVs in autoimmune dry eye have been rarely studied. Methods Small extracellular vesicles from human umbilical cord mesenchymal stem cells (hUC-MSC-sEVs) were subconjunctivally injected to rabbit dry eye model, and their preventive or therapeutical effects were assessed by recording the clinical and histological scores. Quantitative real-time PCR (Q-PCR), western blot and flow cytometry were performed to evaluate the immunomodulatory effects of hUC-MSC-sEVs on macrophages and T regulatory cells (Tregs) both in vivo and in vitro, and the in vitro T cell proliferation was detected by Bromodeoxyuridine (BrdU) assay. In addition, high expression of miR-100-5p in hUC-MSC-sEVs was identified by Q-PCR, and the functional role of sEVs-miR-100-5p on macrophages was explored by a series of co-culture experiments using sEVs derived from hUC-MSCs transfected with miR-100-5p inhibitor. Results We firstly demonstrated that hUC-MSC-sEVs had the preventive and therapeutical effects on rabbit autoimmune dacryoadenitis, an animal model of Sjögren’s syndrome (SS) dry eye. Further investigation revealed that hUC-MSC-sEVs administration effectively elicited macrophages into an anti-inflammatory M2 phenotype and elevated the proportion of Tregs both in vivo and in vitro, which contributed to reduced inflammation and improved tissue damage. Importantly, hUC-MSC-sEVs-educated macrophages with M2-like phenotype exhibited strong capacity to inhibit CD4+ T cell proliferation and promote Treg generation in vitro. Mechanistically, miR-100-5p was highly enriched in hUC-MSC-sEVs, and knockdown of miR-100-5p in hUC-MSC-sEVs partially blunted the promotion of hUC-MSC-sEVs on M2 macrophage polarization and even attenuated the effect of hUC-MSC-sEVs-educated macrophages on T cell suppression and Treg expansion. Conclusion Our data indicated that hUC-MSC-sEVs alleviated autoimmune dacryoadenitis by promoting M2 macrophage polarization and Treg generation possibly through shuttling miR-100-5p. This study sheds new light on the application of MSC-sEVs as a promising therapeutic method for SS dry eye.